(untitled) (International Journal of Ayurveda and Pharma Research, 2017)
A female patient of 26 years old came into the OPD of Prasuti-Tantra at Choudhary Brahm Prakash Ayurveda Charaka Sansathan, Khera Dabar, New Delhi on dated 25/02/2017 with the complaint of wants to conceive since 3 years and scanty flow during menstrual cycle since 1year. On enquiry, she told that, she had miscarriage last year in January 2016 of gestational age 1month 6 days. Her menstrual cycle was irregular with duration of 3-5 days and interval of 28 to 32 days with scanty amount (1 pad/day) of menstrual blood and no other associated symptoms. She gave previous history of allopathic treatment. Her all Investigations regarding infertility had normal study except ultrasonography (USG) report which revealed Low antral follicles count. Aim of the management was to increase the Low Antral Follicles count as it is one of the cause of infertility and which represents poor ovarian reserve. So, the drug Phalasarpi as mentioned by Aacharya Vagbhatta for the conception was selected for Uttra Basti and Oral use as in- vivo effect of Phalasarpi in albino rat has revealed increased Gonadotropin secretion and regulation of the activity of the enzymes involved in ovarian steroidogenesis and stimulates serum estradiol level and proved to be successful in Anovulatory Infertility.